The rivers of milk and honey: quran stories for little hearts - Khan, Saniyasnain (Goodword Books India, 2002)
"The Rivers of Milk and Honey" is a narrative that often symbolizes abundance, prosperity, and divine blessings. It typically describes a promised land or a utopian existence where the needs of the people are met with generosity and kindness. The story highlights themes of hope, fulfillment, and the idea that a harmonious life is achievable through faith and collective effort.